Complete biology for cambridge igcse - Pickering, Ron (Oxford University Press Oxford, 2010)
This second edition provides full coverage of the most recent Cambridge IGCSE syllabus in a highly illustrative and accessible way. It also comes with a free CD, including additional exam style questions, interactive exercises and revision tips. Fully endorsed by Cambridge International Examinations.